2017
DOI: 10.1016/j.ijscr.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal papillary mucinous neoplasm of the pancreas associated with neuroendocrine tumor: A case report

Abstract: HighlightsThe panreatic IPMN and neuroendocrine carcinoma is very unusual.The IPMN component of our patient has high grade dysplasia, which is very rare.In presence of contrast enhancing nodular foci, while evaluating IPMN on imaging studies, possibilty of neuroendocrine tumor should be in mind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Of note, a recent study of a large collection of pancreatic specimens reported that the frequency of the incidental histological diagnosis of P-NEN concomitant with IPMN was as high as 6.4% (13/202 IPMN cases) (5). The study also showed that the number of patients who had a main diagno- (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Of note, the median P-NEN tumor size was 11.5 (range: 2-35) mm.…”
Section: Discussionmentioning
confidence: 90%
“…Of note, a recent study of a large collection of pancreatic specimens reported that the frequency of the incidental histological diagnosis of P-NEN concomitant with IPMN was as high as 6.4% (13/202 IPMN cases) (5). The study also showed that the number of patients who had a main diagno- (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Of note, the median P-NEN tumor size was 11.5 (range: 2-35) mm.…”
Section: Discussionmentioning
confidence: 90%
“…The literature describes some cases of small size NET, accompanied by dilatation of the MPD [ 3 , 7–9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Co-occurrence of IPMN and NET is a very rare entity [ 34 , 35 ] and Boge et al. [36] reported that neuroendocrine carcinoma was identified as a mural nodule measuring 1.5cm in the dilated pancreatic duct and had marked contrast enhancement with on MRI. In the present case, intraductal tumor causes dilatation of the pancreatic duct simply due to tumor mass itself with poor contrast enhancement and has no dilatation of downstream of the tumor owing to mucin hypersecretion.…”
Section: Discussionmentioning
confidence: 99%